2018
DOI: 10.1155/2018/5436187
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenomic Integrative Network Analysis of the Critical Region Associated with Wolf-Hirschhorn Syndrome

Abstract: Deletions in the 4p16.3 region are associated with Wolf-Hirschhorn syndrome (WHS), a contiguous gene deletion syndrome involving variable size deletions. In this study, we perform a cytogenomic integrative analysis combining classical cytogenetic methods, fluorescence in situ hybridization (FISH), chromosomal microarray analysis (CMA), and systems biology strategies, to establish the cytogenomic profile involving the 4p16.3 critical region and suggest WHS-related intracellular cell signaling cascades. The cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…(i) Highlighting a major role of WHSC1 (NSD2) gene in the pathogenesis of the WHS main features (ID, characteristic facies, growth and developmental delay), in fact all these works suggest; that truncating variants on NSD2 gene will lead to atypical clinical manifestations of WHS, not including the epilepsy (Barrie et al, 2019;Boczek et al, 2018;Cammarata-Scalisi et al, 2019;Corrêa et al, 2018;Hirschhorn, 2008;Jiang et al, 2019):…”
Section: A Further Updatementioning
confidence: 99%
“…(i) Highlighting a major role of WHSC1 (NSD2) gene in the pathogenesis of the WHS main features (ID, characteristic facies, growth and developmental delay), in fact all these works suggest; that truncating variants on NSD2 gene will lead to atypical clinical manifestations of WHS, not including the epilepsy (Barrie et al, 2019;Boczek et al, 2018;Cammarata-Scalisi et al, 2019;Corrêa et al, 2018;Hirschhorn, 2008;Jiang et al, 2019):…”
Section: A Further Updatementioning
confidence: 99%
“…The investigation of protein-coding genes located in the critical regions of chromosomes using a platform of PPI indicated that MSNproteins were likely to be located in specific regions of the interactome (Corrêa et al, 2018;Corrêa, Feltes, Poswar, & Riegel, 2020;Corrêa, Feltes, & Riegel, 2019;Corrêa, Venâncio, Galera, & Riegel, 2020). Disease-associated proteins usually interact with each other in a local neighborhood of the human interactome more frequently than expected by chance (Goh et al, 2007;Oti et al, 2006;Vidal et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this search suggest that the genes affected by copy number variation at each of these four loci play important roles in a variety of biological processes that associated with physiology both in the brain and the heart (Figure 5A). It follows, therefore, that the deletion/duplication of genetic locus involved in these functions may critically disrupt pathways involved in both heart and brain development (Figure 5B), potentially by a complex molecular mechanism (23)(24)(25)(26). Additionally, disruption to heart development may have secondary consequences for brain development.…”
Section: Functional Analysis Of Significant Cnvsmentioning
confidence: 99%